A Survey on Security and Various Attacks in Wireless Sensor Network - Sengar, P; Bhardwaj, N (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor networks (WSN) have a set of algorithms and protocols with self-establishing capabilities. These sensors work with every other to sense some physical phenomenon after which the information gather is processed to get relevant outcomes. These sensor nodes can calculate, sense, and assemble particulars from the atmospheres and based on some neighborhood decision process, they are able to transmit the sensed records to the person. The battery is the main electricity supply in a sensor node and secondary power supply that harvests strength from the atmospheres together with solar panels may be added to the node depending on the appropriateness of the atmospheres where the sensor will be diffuse. Clustering is the technique which performs the grouping of similar nodes and then starts communicating into the clusters. Security can be achieved by encrypting and decrypting the data and make them unable to read that from the malicious users. Cryptography is the useful technique which contains symmetric and asymmetric methods. In this paper we study about WSN and its application or various attacks which exist in the sensor network in the middle of paper we discuss various existing technique and it’s working. Various attacks are performed in this network such as passive and active attacks or insider and outsider attacks. The wirelessly network always required security in the form of data integrity, confidentiality, authenticity and etc.